Handbook of functional dairy products (CRC Press, 2003)
The book explores the product development process and the market dynamics driving product innovation. With an emphasis on the potential contribution of functional dairy products in the maintenance of health and prevention of disease, chapters examine specific ingredients and products, safety and technology issues, the impact of biotechnology, the regulatory environment, and the communication of health benefits.